Challenges for deliberative democracy in the digital era - Grecu, Silviu-Petru; Chiriac , Horia Costin (Technium Social Sciences Journal, 2021)
The aim of this paper is to create a deep radiography of the evolution of deliberative democracy in the digital era. The increased number of on-line media, social dynamics and economic variables could be seen as several structural challenges for the quality of the deliberative democracy. Starting from these premises the study has several research objectives as: i. to analyse the impact of deliberative democracy in EU countries; ii. to estimate the magnitude of the statistical association between deliberative component of the democracy and on-line media; iii. the impact of economic development on the evolution of deliberative democracy and on-line communication. The main research questions are: “how could on line media determine the decreasing level of deliberative democracy?” and “is political polarization the effect of the on-line media fractionalization?” Empirical findings present the image of the EU political systems in terms of “flawed democracy” with the mean of Democracy Index= 7.34. At the inferential level we have determined several linear and non-linear equations of regression as: deliberative democracy and on-line media fractionalization, a negative relation with R2= 0.673, p=0.01.Also, the main predictor of the quality of the democracy in conditions of the increased number of on-line media is represented by the social and political polarization. Economic determinants are statistically significant for the dynamics of the deliberative democracy (R2=0.465, p<0.001).